Negotiating the Resolution of the Conflict over the Establishment of the GKPI Church in Lohsari Hamlet, Perlabian Village, Kampung Rakyat District, South Labuhanbatu Regency (2016–2023) - Fahrizal Putra Pulungan; Irwansyah (UNIVERSITAS PAKUAN, 2026)
Conflicts over the establishment of places of worship remain a recurring social issue in Indonesia’s multicultural societies, including the conflict regarding the construction of the Gereja Kristen Protestan Indonesia (GKPI) church in Lohsari Hamlet, Kampung Rakyat District, South Labuhanbatu Regency. This study aims to analyze the negotiation process in resolving the conflict over the establishment of the GKPI church and to identify the actors, strategies, and factors that influence the success of the negotiation process. This research employs a qualitative approach with data collection techniques including in-depth interviews, observation, and documentary analysis. The results show that the negotiation process involved various parties, including church administrators, community leaders, religious leaders, the village government, and security officials. The negotiations were conducted through dialogue, deliberation, and mediation by emphasizing the principles of tolerance, compliance with regulations, and efforts to maintain social stability. Although the process faced several obstacles, such as differences in perceptions and interests among the parties involved, the negotiation process was able to prevent the conflict from escalating and create opportunities for compromise. This study concludes that inclusive negotiation based on participatory communication plays an important role in resolving conflicts related to the establishment of places of worship in pluralistic societies.